2006
DOI: 10.1080/10286020500044732
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of crocin against endothelial injury induced by hydrogen peroxidein vitro

Abstract: Crocin, the digentiobiosyl ester of crocetin, was investigated for its cytoprotective effect on hydrogen peroxide-induced injury in bovine aortic endothelial cells (BAECs). The morphology of BAECs was observed by inverted phase contrast and electron microscopy. The MTT assay was used to measure cell viability. Cell apoptosis was evaluated by DNA argarose gel electrophoresis. The cells treated with H(2)O(2) (200 microM) showed apoptotic changes as revealed by cell shrinkage, condensation of nuclei, membrane ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 10 publications
3
27
0
4
Order By: Relevance
“…Crocin might attenuate activation of T cells and microglial within the CNS during EAE. In addition, with crocin's documented anti-inflammatory effects (50,51), it might also modulate blood-brain barrier permeability, possibly through suppression of inflammation-induced cell adhesion molecules on brain endothelia such as ICAM2, VCAM, or one of the integrins (44,52). Crocin also ameliorated the EAE disease profile with a concurrent decrease in maximum and cumulative scores.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Crocin might attenuate activation of T cells and microglial within the CNS during EAE. In addition, with crocin's documented anti-inflammatory effects (50,51), it might also modulate blood-brain barrier permeability, possibly through suppression of inflammation-induced cell adhesion molecules on brain endothelia such as ICAM2, VCAM, or one of the integrins (44,52). Crocin also ameliorated the EAE disease profile with a concurrent decrease in maximum and cumulative scores.…”
Section: Discussionmentioning
confidence: 90%
“…The pathobiological effects of astrocytic Syncytin-1 overexpression on oligodendrocyte viability were ameliorated by concurrent treatment with crocin. Crocin has been shown to exert neuroprotective effects in several model systems, possibly through suppression of free radical production (50)(51)(52). More recently, crocin has been reported to suppress microglial activation (53) and ER stress (54).…”
Section: Discussionmentioning
confidence: 99%
“…35 With regard to the reduction of pancreatic apoptosis through decreasing p53 expression levels, effect of crocin may be related to the antioxidant properties and its effects in reducing blood glucose and HbA1c levels. In addition, Xu et al (2006)demonstrated that crocin has preventive effects on the cell apoptosis induced by hydrogen peroxide through antagonising apoptosis. 36 Thus, hara et al (2013) suggested that crocin protects platelets from oxidative stressinduced apoptosis through reducing H2O2-evoked activation of caspase-3 (pro-apoptotic protein).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xu et al (2006)demonstrated that crocin has preventive effects on the cell apoptosis induced by hydrogen peroxide through antagonising apoptosis. 36 Thus, hara et al (2013) suggested that crocin protects platelets from oxidative stressinduced apoptosis through reducing H2O2-evoked activation of caspase-3 (pro-apoptotic protein). 37 Therefore we suggest that the anti-apoptotic effect of crocin may due to antioxidant effects, lowering blood glucose and reduction of p53 protein in pancreas tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Συγκεκριμένα μείωσε κατά 40% τις προκαλούμενες από την αφλατοξίνη ηπατικές αλλοιώσεις και ελάττωσε τα επίπεδα της ασπαρτικής αμινοτρανσφεράσης (AST), της αλανινικής αμινοτρανσφεράσης (ALT), της αλκαλικής φωσφατάσης (ALP) και της γ-γλουταμινοτρανσπεπτιδάσης (γ-GT) στον ορό (Pellegrini et al, 2006;Assimopoulou et al, 2005;Papandreou et al, 2006;Chen et al, 2008;Xu et al, 2006;Kanakis et al, 2009;Ordoudi et al, 2009;Asdaq & Inamdar, 2010 .…”
Section: βιολογικές δράσειςunclassified